Physicochemical profile of selected Malaysian honey and the effect of pineapple honey on obesity in vitro and in vivo models / Suhana Samat - Samat, Suhana (2022)
Obesity has become a worldwide problem that can lead to various chronic diseases due to unhealthy diet and lifestyle. Honey has been identified as a food that has a positive effect in combating obesity. In this study, the effect of pineapple honey in combating obesity was investigated using in vivo and in vitro models. The study started with a preliminary screening of selected honeys, namely gelam, acacia and pineapple honeys and two adulterated honeys available in the market. Physicochemical analysis revealed that gelam honey had the highest content of phenolic compounds and flavonoids, followed by pineapple honey. Meanwhile, parameters such as sugar profiles, HMF, and glucose oxidase activity tested for adulterated honey A and B did not fulfil standard quality factors set by the IHC Honey Board.The effect of honey in in vitro studies showed that Gelam, Acacia and pineapple honey at 25% v/v and above significantly (p < 0.05) inhibited adipogenesis in 3T3-L1 adipocytes by reducing lipid accumulation, Feret diameter and intracellular triglyceride content. In addition, Gelam, Acacia and pineapple honey significantly reduced the concentrations of leptin and resistin. The results suggest that honey may be involved in the control of adipocytokines in the process of adipogenesis. In vivo studies showed no abnormal changes in acute and subacute studies after administration of Acacia, Gelam and pineapple honey. In addition, obese rats fed pineapple honey (HFDPH) and orlistat (HFDO) had an obesity index ~4% lower than the HFD group